Blood and chocolate - Klause, Annette Curtis (New York, N.Y. : Laurel-Leaf Books/Bantam Doubleday Dell Books for Young Readers, 1999)
Having fallen for a human boy, a beautiful teenage werewolf must battle both her packmates and the fear of the townspeople to decide where she belongs and with whom.
"Laurel-leaf books."
"Reprinted by arrangement with Delacorte Press ... October 1999"--T.p. verso.
Reading level: 5.9.
Keywords: Werewolves -- Juvenile fiction; Horror tales; Science fiction